Implantation of parathyroid and parathyroid adenomas prior "in vitro" implant clearance - Goyena, Horacio; Larre Borges, Uruguay; Cazabán, Luis A; Mate, Miguel; Mesa, Guillermo (Cirugía del Uruguay, 1972)
Two functioning parathyroid adenomas and one human parathyrJ1 i were used for a transplant, previous culturation "in vitro" of the fragments. A dispositive hased in the method described by Trowell that per1r.itted a relatively good conservation was used. The srrum of the donor was gradually substituted in the medium by that of the receiver in order to "adapt the tissue to the chemistry of the host". The results were more satisfactory in the case of the patient treated with adenoma and parathyroid gland.